Dictionary of biblical imagery - Ryken, Leland; Wilhoit, Jim.; Longman, Tremper; Duriez, Colin; Penney, Douglas, 1956-; Reid, Daniel G., 1949- (Downers Grove, Ill. : InterVarsity Press, 1998)
The Dictionary of Biblical Imagery is dedicated to exploring the images, symbols, motifs, metaphors and literary patterns found in the Bible. It examines the Bible's universal archetypes or master images--including the plot motifs and character types that recur throughout life, literature and the Bible. --From publisher's description.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Bible -- Language, style -- Dictionaries; Symbolism in the Bible -- Dictionaries; Bible -- Language, style; Symbolism in the Bible; Bible -- Langue -- Dictionnaires anglais; Bible -- Dictionnaires anglais; Symbolisme dans la Bible -- Dictionnaires anglais; Bijbel; Beeldspraak; Archetypen; Metaforen; Bible -- Langue -- Dictionnaires; Symbolisme dans la Bible -- Dictionnaires; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books